Smallholder farms in eastern African tropical highlands have low soil greenhouse gas fluxes - Pelster, David (2017)
Few field studies examine greenhouse gas (GHG) emissions from African agricultural systems, resulting in high uncertainty for national inventories. This lack of data is particularly noticeable in smallholder farms in sub-Saharan Africa, where low inputs are often correlated with low yields, often resulting in food insecurity as well. We provide the most comprehensive study in Africa to date, examining annual soil CO2, CH4 and N2O emissions from 59 smallholder plots across different vegetation types, field types and land classes in western Kenya. The study area consists of a lowland area (approximately 1200ma.s.l.) rising approximately 600m to a highland plateau. Cumulative annual fluxes ranged from2.8 to 15.0MgCO2-Cha-1,-6.0 to 2.4kgCH4-Cha-1 and-0.1 to 1.8kgN2O-Nha-1. Management intensity of the plots did not result in differences in annual GHG fluxes measured (P Combining double low line 0.46, 0.14 and 0.67 for CO2, CH4 and N2O respectively). The similar emissions were likely related to low fertilizer input rates (≤20kgNha-1). Grazing plots had the highest CO2 fluxes (P Combining double low line 0.005), treed plots (plantations) were a larger CH4 sink than grazing plots (P Combining double low line 0.05), while soil N2O emissions were similar across vegetation types (P Combining double low line 0.59). This study is likely representative for low fertilizer input, smallholder systems across sub-Saharan Africa, providing critical data for estimating regional or continental GHG inventories. Low crop yields, likely due to low fertilization inputs, resulted in high (up to 67gN2O-Nkg-1 aboveground N uptake) yield-scaled emissions. Improvement of crop production through better water and nutrient management might therefore be an important tool in increasing food security in the region while reducing the climate footprint per unit of food produced.